UJI AKTIVITAS ANTIOKSIDAN FRAKSI N-HEKSAN, KLOROFORM DAN ETIL ASETAT DARI EKSTRAK ETANOL UMBI PAKU ATAI MERAH (Angiopteris ferox Copel) - Reksi Sundu; Fitri Handayani; Sapri; Henny Nurhasnawati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Antioxidants play an important role as a health protection factor. One of the plants that have the potential as a natural antioxidant is the red paku atai tuber (Angiopteris ferox Copel). The purpose of this study was to determine the antioxidant activity of the n-hexane, chloroform and ethyl acetate fraction from ethanol extract of red paku atai tuber. The method in this study was DPPH (1,1-diphenyl-2-picrylhydrazyl) method using UV-Visible spectrophotometer. The results of this study showed that the extract of ethanol from red paku atai tuber n-hexane fraction had IC50 values of 884.14 ppm (weak category); chloroform of 199.72 ppm (weak category); ethyl acetate of 18.81 ppm (very strong category) while vitamin C as comparison was 5.09 ppm (very strong category).